The meaning of blood and cerebrospinal fluid biomarkers in early diagnosis of Alzheimer's disease - Julita Szarpak; Weronika Dalmata; Ilona Gąbka; Daria Madycka; Olga Wysokińska (Kazimierz Wielki University, 2020)
Introduction and purpose: Alzheimer's disease (AD) belongs to the group of neurodegenerative diseases and is the leading cause of dementia worldwide. Its development includes the impact of genetic, metabolic and environmental factors. Despite high prevalence of Alzheimer's disease and dynamic development of medical science, there is currently no clinically proven causal treatment. The proposed therapies are only symptomatic. However, there is a wide set of substances known as biomarkers that are detected in the blood or in the cerebrospinal fluid (CSF) in the stages preceding full-blown Alzheimer's disease. Brief description of the state of knowledge: In order to obtain material for CSF examination, a lumbar puncture must be performed. It is an invasive procedure, with the risk of complications such as bleeding into the spinal cord, infection or even nerve damage. Obtaining a blood sample for testing specific indicators is less invasive and more widely available. Currently, the diagnostic significance of commonly known markers arising in the progress of the AD pathological process, such as amyloid β, tau protein and its phosphorylated form or β-secretase, is being investigated. As the knowledge on the pathogenesis of AD grows, further markers such as ubiquitin, micro RNA or plasma neurofilament light are tested. Conclusions: There is a collection of biomarkers that can perform a diagnostic function for Alzheimer's disease. Due to the advantages of blood and plasma testing, basing the diagnosis of early forms of AD on these tests seems to be particularly interesting. However, the use of biomarkers on a global scale requires further research and test standardization, as well as the development of guidelines for their interpretation.